Changes in tissue sodium concentration and sodium relaxation times during the maturation of human knee cartilage: Ex vivo 23Na MRI study at 10.5 T - Zbýň, Štefan; Ludwig, Kai D.; Watkins, Lauren E.; Lagore, Russell L.; Nowacki, Amanda; Tóth, Ferenc; Tompkins, Marc A.; Zhang, Lin; Adriany, Gregor; Gold, Garry E.; Shea, Kevin G.; Nagel, Armin Michael; et al. (Magnetic Resonance in Medicine, 2023)
Purpose: To evaluate the influence of skeletal maturation on sodium (23Na) MRI relaxation parameters and the accuracy of tissue sodium concentration (TSC) quantification in human knee cartilage. Methods: Twelve pediatric knee specimens were imaged with whole-body 10.5 T MRI using a density-adapted 3D radial projection sequence to evaluate 23Na parameters: B1+, T1, biexponential (Formula presented.), and TSC. Water, collagen, and sulfated glycosaminoglycan (sGAG) content were calculated from osteochondral biopsies. The TSC was corrected for B1+, relaxation, and water content. The literature-based TSC (TSCLB) used previously published values for corrections, whereas the specimen-specific TSC (TSCSP) used measurements from individual specimens. 23Na parameters were evaluated in eight cartilage compartments segmented on proton images. Associations between 23Na parameters, TSCLB − TSCSP difference, biochemical content, and age were determined. Results: From birth to 12 years, cartilage water content decreased by 18%; collagen increased by 59%; and sGAG decreased by 36% (all R2 ≥ 0.557). The short (Formula presented.) ((Formula presented.)) decreased by 72%, and the signal fraction relaxing with (Formula presented.) ((Formula presented.)) increased by 55% during the first 5 years but remained relatively stable after that. TSCSP was significantly correlated with sGAG content from biopsies (R2 = 0.739). Depending on age, TSCLB showed higher or lower values than TSCSP. The TSCLB − TSCSP difference was significantly correlated with (Formula presented.) (R2 = 0.850), (Formula presented.) (R2 = 0.651), and water content (R2 = 0.738). Conclusion: TSC and relaxation parameters measured with 23Na MRI provide noninvasive information about changes in sGAG content and collagen matrix during cartilage maturation. Cartilage TSC quantification assuming fixed relaxation may be feasible in children older than 5 years.
CRIS-Team Scopus Importer:2023-12-01
Keywords: 10.5 T; biochemical composition of cartilage; knee cartilage maturation; sodium (; tissue sodium concentration